Determination of Chlorpyrifos in Human Blood by Gas Chromatography-Mass Spectrometry - Xinhua Dai; Fei Fan; Yi Ye; Fan Chen; Zhigui Wu; Xiang Lu; Qingtao Wei; Jianxia Chen; Youyi Yan; Linchuan Liao (Wolters Kluwer Medknow Publications, 2017)
Gas chromatography-mass spectrometry method was developed for the qualitative and quantitative analyses of chlorpyrifos in human blood samples. The chlorpyrifos and parathion (internal standard) in human blood were extracted with a mixed solvent of hexane and acetonitrile. Chlorpyrifos was well separated from the internal standard. The linear range of chlorpyrifos was 0.01-2 μg/ml in blood. The limit of detection and limit of quantification were estimated at 0.002 and 0.01 μg/ml, respectively. The inter- and intra-day precisions, accuracy, and recovery were assessed to verify this method. The results showed that the developed method is rapid, sensitive, and reliable. It is suitable for the determination of chlorpyrifos in forensic toxicological analysis and clinical diagnosis.